Multifilaments based on partially miscible polymers blend filled with carbon nanotubes. Issue 1 (1st January 2023) - Regnier, J; Cloarec, C; Cayla, A; Campagne, C; Devaux, E
Abstract: Many textile fields, such as industrial structures or clothing, use the electrical conductivity variation of yarns to detect fluid leakage. Such yarns can be developed by melt spinning conductive polymer composites (CPC). CPC filaments are composed of a polymer's matrix which is blended with sufficient quantity of electrically conductive fillers to make the filament conductive. To combine properties or improve the compounds preparation, more and more studies are investigating different polymers blends. In this study, CPC monofilaments and multifilaments are developed and characterized to observe the formulation influence on spinnability and the implementation process on the water detection. Two principles of water detection are studied on the CPC which is composed of a blend of partially miscible polymers (polyethylene terephthalate (PET)/polybutylene terephthalate (PBT)) filled with carbon nanotubes (CNT). The principle of absorption is based on the electrical conductivity variation of the filament in contact with water. For the short circuit principle, the presence of the liquid is detected when the water creates a conductive path between two filaments in parallel.